Insights into head-column field-amplified sample stacking: Part II. Study of the behavior of the electrophoretic system after electrokinetic injection of cationic compounds across a short water plug - Šesták, Jozef; Thormann, Wolfgang (Journal of chromatography. A, Including electrophoresis and other separation methods, 2017)
Part I on head-column field-amplified sample stacking comprised a detailed study of the electrokinetic injection of a weak base across a short water plug into a phosphate buffer at low pH. The water plug is converted into a low conductive acidic zone and cationic analytes become stacked at the interface between this and a newly formed phosphoric acid zone. The fundamentals of electrokinetic processes occurring thereafter were studied experimentally and with computer simulation and are presented as part II. The configuration analyzed represents a discontinuous buffer system. Computer simulation revealed that the phosphoric acid zone at the plug-buffer interface becomes converted into a migrating phosphate buffer plug which corresponds to the cationically migrating system zone of the phosphate buffer system. Its mobility is higher than that of the analytes such that they migrate behind the system zone in a phosphate buffer comparable to the applied background electrolyte. The temporal behaviour of the current and the conductivity across the water plug were monitored and found to reflect the changes in the low conductivity plug. Determination of the buffer flow in the capillary revealed increased pumping caused by the mismatch of electroosmosis within the low conductivity plug and the buffer. This effect becomes elevated with increasing water plug length. For plug lengths up to 1% of the total column length the flow quickly drops to the electroosmotic flow of the buffer and simulations with experimentally determined current and flow values predict negligible band dispersion and no loss of resolution for both low and large molecular mass components.
Keywords: Cations; Phosphoric Acids; Computer Simulation; voda; Electrolytes; elektrolyty; Water; kationty; kyseliny fosforečné; pufry; elektroosmóza; Buffers; Electrophoresis, Capillary; počítačová simulace; elektroforéza kapilární; Electroosmosis